High technology spin-offs from government R&D laboratories and research universities - Carayannis, Elias G. (Technovation)
Following a study of seven spin-off organizations in New Mexico and Japan, the authors suggest a more complex definition of 'spin-off' expanding somewhat on the current definition which centres on technological innovation and entrepreneurs.